Is there an Influence of Work Engagement on Job Satisfaction? A Literature Review - Widyastuti, Pratiwi; Wahyuningsih, Sri Handari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper aims to identify research trends on Job Engagement and Job Satisfaction globally. The Method used in this study is qualitative research with a literature study approach. As for the data found, 229 documents were obtained and analyzed 2014-2023. This dataset was converted to CSV format andfor Bibliometrix in the analysis using VOSviwer. This study's findings show that the research trend from 2014 to 2023 indexed by Scopus has increased. The United States is the country that most influences scientific journals with a focus on the role of leadership that helps increase Job Engagement and Satisfaction. Taris, T.W. is the most prolific author with 4 Work Engagement and Job Satisfaction documents. His work focuses on the relationship between interpersonal forgiveness and workplace outcomes. Furthermore, topics such as Employee well-being, Happiness at Work, Workaholism, Job Resources, and Organizational Identification are still open for further research. Ongoing research trends show how effective it is to address real issues and needs in the workplace. This shows that academics and practitioners continue to explore and understand the dynamics of Work Engagement and Job Satisfaction. The main limitation of this study should be considered - the use of data derived only from the Scopus database. This paper reveals the research trends and research areas of Job Engagement and Job Satisfaction. The results help scholars quickly understand leadership performance research on job satisfaction. The paper also provides an alternative approach to conducting a literature review with a computer-aided analysis program